Endoscopic Coil Embolization for Refractory Intrahepatic Biliary Duct Leak. Issue 2 (23rd February 2022) - Dutra, Barbara; Welborn, Macartney; Thosani, Nirav C.; Badillo, Ricardo; DaVee, Tomas; Bhakta, Dimpal
ABSTRACT: Bile leaks may be seen after blunt and penetrating trauma, as well as iatrogenic injury from surgical procedures. There are many articles on endoscopic treatment options for the management of biliary leaks, including sphincterotomy, endoscopic stent, or nasobiliary drain placement. Data, however, are scarce regarding the management of persistent biliary leaks after the initial intervention. We present a case of endoscopic coil embolization to treat a refractory bile leak after initial endoscopic sphincterotomy and stent placement in a patient with a grade IV liver laceration due to a gunshot wound.